BIOLOGICAL DIVERSITY IN THE HYDROSPHERE SHELL AND ITS SIGNIFICANCE IN NATURE (Global Conference on Medical and Health Sciences, 2026)
This article discusses the hydrosphere, one of the earth's crusts, and its importance on the earth's surface, the level of biodiversity, the role of water resources in the development of organisms, and concepts related to natural sciences, ecology, in particular, biodiversity. In addition, information about the world's oceans and seas, the diversity of various organisms adapted to different conditions, the relationship between biomasses, the higher biomass of aquatic organisms than terrestrial organisms, the beauties of nature, the importance of the hydrosphere in educating young people to love nature and protect natural resources, are also discussed.
Keywords: ocean, sea, plant, animal, biodiversity, algae.